HUBUNGAN PENGETAHUAN, PERAN DAN PENDIDIKAN ORANG TUA TERHADAP PERKEMBANGAN PSIKOSEKSUAL ANAK USIA 2-6 TAHUN DI PUSKESMAS WARINGIN KURUNG TAHUN 2019 - Ika Apriyanti; Halimah Tu’sadiah; Evi Avicenna Agustin (Poltekkes 'Aisyiyah Banten, 2020)
The development phase at 2-6 years of age is the preschool, when children begin to have an awareness of themselves as male or female, can regulate themselves in bowel movements. Based on preliminary studies conducted on parents who have children aged 2-6 years, amounting to 25 people, obtained as many as 20 parents (80%) Psychosexual Development of Children aged 2-6 years undeveloped and 5 parents (20%) Psychosexual Development of Children Ages 2-6 years have developed. Then from 20 parents (75%) do not know about what parents should teach and the role of parents in children 2-6 years in the development of their child's sexuality (25%). This study aims to determine the relationship of knowledge, roles and education of parents in the psychosexual development of children aged 2-6 years at the Waringinkurung Health Center. This research is an analytical survey with cross sectional time approach, a sample of 98 people. The results of research on psychosexual development are not yet developed (36.7%), low knowledge (40.82%), lack of parental role (22.4%), basic education (21.4%). There was no relationship between knowledge (p = 1,000), and there was a relationship between roles (p = 0.005), education level (p = 0.002) to the psychosexual development of children aged 2-6 years. Parents are expected to be able to improve and be able to guide children according to their development and according to their needs properly including gender, male and female differences and can regulate bowel movements and can teach children according to language that is easily understood